Sharia Compliance Analysis of Gold Pawn Products at BMT UGT Nusantara Muncar Branch A Fiqh Muamalah Perspective - Siti Muafatunisa; Retno Evi Fitriani; Lilit Biati (ICO EDUSHA, 2025)
This study aims to analyze the implementation of Sharia Gold Pawn Financing at BMT UGT Nusantara Muncar Branch and evaluate its compliance with Islamic muamalah principles.Qualitative case study approach was employed, utilizing observation and in-depth interviews with the branch manager, focusing on the application of three core contracts: Qardh, Rahn, and Ijarah. The findings reveal that the Qardh contract serves as the loan foundation, while Rahn functions as the gold collateral mechanism. However, a critical sharia non-compliance was identified in the Ijarah contract, where the service fee (ujrah) is calculated based on the financing amount rather than the gold weight, contradicting DSN-MUI Fatwa No. 09/2000 and SE BI 14/2012. Other contractual elements, such as object clarity, mutual consent (rida), and obligation fulfillment, generally met sharia requirements. While Qardh and Rahn implementations are sharia-compliant, an urgent adjustment to the Ijarah-based fee structure is necessary to ensure full adherence to Islamic law and prevent potential riba. The study recommends aligning ujrah calculation with gold weight and strengthening internal sharia governance.